Exploring the Nature of Students as Pedagogical Beings: A Humanistic Approach in Education - Rosdiana Rosdiana; Yuspiani Yuspiani; Alwan Subhan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2025)
The humanistic approach in education emphasizes the holistic development of learners, encompassing emotional, social, and academic aspects. The library research method was chosen because the study focuses on exploring concepts and theories regarding the humanistic approach in education as well as the nature of students as pedagogical beings. This study examines the benefits, challenges, and implementation strategies of the humanistic approach within the context of modern education. Findings reveal that this approach enhances learners’ motivation, creativity, and confidence, while fostering self-awareness and social responsibility. However, successful implementation requires adequate resources and proper teacher training. This study recommends strengthening teacher training, providing sufficient resources, and fostering collaboration among stakeholders to support the sustainability of the humanistic approach in education. Thus, the humanistic approach can contribute to producing learners who excel not only intellectually but also emotionally and socially.